Pulmonary exacerbations as a risk factor for lung function decline – experiences of the National Cystic Fibrosis Center - Gojsina, Bojana Z; Rodic, Milan; Visekruna, Jelena; Trajkovic, Goran Z; Sovtic, Aleksandar D; Minic, Predrag B (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Pulmonary exacerbations have negative impact on clinical course of cystic fibrosis (CF) lung disease being associated with a steeper decline in the lung function, unfavorable prognosis and impaired quality of life. The aim of this study was to determine whether an increased number of exacerbations had influence on the lung function in the patients with CF, as well as to estimate the nutritional status, gender, presence of comorbid conditions and bacterial colonization of airways as predictive factors for pulmonary exacerbations. Methods. This retrospective cohort study included 83 pediatric and adult patients, treated from 2011–2015 in the Mother and Child Health Institute of Serbia „Dr Vukan Čupić”. The best result of forced expiratory volume in the first second (FEV1) and forced vital capacity (FVC) in each year of follow-up was taken into account to calculate the five-year trend values of these indicators. The number of exacerbations per year of follow-up and its impact on the FEV1 decline was evaluated. Results. Mean annual decline of FEV1 and FVC were 2.4% and 1.7% respectively. The malnourished patients had the lower initial values of FEV1 and FVC, and more frequent exacerbations in comparison with the normal weight and overweight patients. The frequency of exacerbations was significantly higher in the patients chronically colonized with Burkholderia cepacia (p = 0.023). The increased number of exacerbation was proved to be the most important factor in a prediction of FEV1 decline over time (p = 0.013). Conclusion. Pulmonary exacerbations lead to the more progressive lung function decline in the patients with CF. Malnourishment and chronic airway colonization with Burkholderia cepacia result in more frequent pulmonary exacerbations.